Corporate Governance, Cash holdings and Value of a Firm: Evidence from Australian Firms - Yarram, Subba Reddy (Information Management and Business Review, 2012)
The present study analyses influence of board structure and cash holdings on the value of Australian firms for the period 2004 to 2010. Australian Stock Exchange (ASX) adopted the Principles of Good Corporate Governance Guidelines in 2003 and Australian firms have started adopting these principles starting 2004. Similarly the reporting framework of Australian firms is harmonized with the rest of the world with adoption of Australian International Financial Reporting Standards (AIFRS) starting in 2004. Corporate cash holdings despite their significance have not been considered extensively in prior literature outside the US. Cash holdings may have significant influence on the value of the firm as too much excess cash may lead to misuse of these funds by entrenched managers. Corporate governance has a role to play in maintaining appropriate cash holdings and their use. The present has two objectives: it considers the influence of corporate cash holdings on the value of Australian firms; and it examines the role of board structure on the relationship between cash holdings and value of the firm. The present study considers all non-financial firms that are part of the All Ordinaries Index (AOI). The present study constructs Fama French 25 portfolio and estimate the excess return as the difference between actual return and the average return of the relevant FF portfolio. OLS analyses show that board independence has no significant impact on the value of the firm though cash holdings have significant influence. Analysing using panel data methods however unearth the significant influence of board independence on the value of Australian firms.